The pathophysiology and treatment of delayed cerebral ischaemia following subarachnoid haemorrhage. Issue 12 (20th May 2014) - Budohoski, Karol P; Guilfoyle, Mathew; Helmy, Adel; Huuskonen, Terhi; Czosnyka, Marek; Kirollos, Ramez; Menon, David K; Pickard, John D; Kirkpatrick, Peter J
Abstract : Cerebral vasospasm has traditionally been regarded as an important cause of delayed cerebral ischaemia (DCI) which occurs after aneurysmal subarachnoid haemorrhage, and often leads to cerebral infarction and poor neurological outcome. However, data from recent studies argue against a pure focus on vasospasm as the cause of delayed ischaemic complications. Findings that marked reduction in the incidence of vasospasm does not translate to a reduction in DCI, or better outcomes has intensified research into other possible mechanisms which may promote ischaemic complications. Early brain injury and cell death, blood-brain barrier disruption and initiation of an inflammatory cascade, microvascular spasm, microthrombosis, cortical spreading depolarisations and failure of cerebral autoregulation, have all been implicated in the pathophysiology of DCI. This review summarises the current knowledge about the mechanisms underlying the development of DCI. Furthermore, it aims to describe and categorise the known pharmacological treatment options with respect to the presumed mechanism of action and its role in DCI.